Ensino de história no Instituto Histórico e Geográfico Brasileiro: as idéias de Agostinho Marques Perdigão Malheiro Filho (1850) e Américo Brasiliense de Almeida e Mello (1876) - Reis, Aaron Sena Cerqueira (2013)
With this dissertation, I intend to infer the idea of History teaching in Instituto Histórico e Geográfico Brasileiro (IHGB) in the period from 1850 to 1876 by analyzes of critic works and textbooks. Published in the Revista do IHGB, the critic works prepared by the commission of History evaluated two works whose authors stressed their didactics uses: the Índice cronológico (1850) by Agostinho Marques Perdigão Malheiro Filho and the Lições de História Pátria (1876) by Américo Brasiliense de Almeida e Mello. Imbuing me of a critical spirit, I try to understand the representation of sources in order to know its characteristics, whether or not didactic, and its authors, whether or not educators. Finally, I make a comparison between the concepts expressed in different documents.